2006
DOI: 10.1111/j.1740-8709.2006.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, feasibility and affordability of infant feeding options for HIV‐infected women: a qualitative study in south‐west Nigeria

Abstract: The objective of this study was to explore the acceptability, feasibility, affordability, safety and sustainability of replacement feeding options for HIV-infected mothers in Ile-Ife, in south-west Nigeria. Six focus group discussions were conducted with a purposive sample of mothers, fathers and grandmothers. The HIV status of all participants was unknown to investigators. All text data were analysed using the Text-based Beta Software program. With regard to the acceptability of replacement feeds, respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
3
25
0
3
Order By: Relevance
“…69 Water supplementation of breastfeeding is deeply engrained in Africa, as most infants are given water from birth, in part due to cultural perceptions that infants need water to survive. 70 Similar to the finding of this study, Scariati et al 71 submitted that water supplementation of neonates was a prevalent practice among a cohort of US women.…”
Section: Discussionsupporting
confidence: 76%
“…69 Water supplementation of breastfeeding is deeply engrained in Africa, as most infants are given water from birth, in part due to cultural perceptions that infants need water to survive. 70 Similar to the finding of this study, Scariati et al 71 submitted that water supplementation of neonates was a prevalent practice among a cohort of US women.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, mixed feeding is adopted in some instances when colic is associated with hunger and inadequate breast milk (Thairu et al, 2005;Webb-Girard et al, 2012;Madiba et al, 2013). In some parts of Nigeria and Uganda however, breast milk is considered food, however water is considered a necessary supplement (Abiona et al, 2006;Fadnes et al, 2010). There were similar findings in Kenya where water is considered as "necessary for life" (Webb-Girard et al, 2012).…”
Section: Maternal Health Food Insecurity and Insufficient Breast Milmentioning
confidence: 95%
“…In Nigeria, participants in one study believed that HIV-positive mothers might be too ill to breastfeed exclusively (Abiona et al, 2006). Studies from South Africa, Malawi and Kenya, also suggest that many women will practice mixed feeding with solids or semi-solid foods because they do not consider breast milk to be food and therefore question its nutritional value (Buskens et al, 2007;Wachira et al, 2009;Mataya et al, 2013).…”
Section: Maternal Health Food Insecurity and Insufficient Breast Milmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that barriers to replacement feeding (instead of breastfeeding) included: the high cost of replacement feeds and fuel for cooking; unreliable supply of electricity; poor access to safe water, and poor access to storage facilities [49] .…”
Section: Who Guidelinesmentioning
confidence: 99%